2012
DOI: 10.4161/adip.21756
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic alterations following visceral fat removal and expansion

Abstract: Increased visceral adiposity is a risk factor for metabolic disorders such as dyslipidemia, hypertension, insulin resistance and type 2 diabetes, whereas peripheral (subcutaneous) obesity is not. Though the specific mechanisms which contribute to these adipose depot differences are unknown, visceral fat accumulation is proposed to result in metabolic dysregulation because of increased effluent, e.g., fatty acids and/or adipokines/cytokines, to the liver via the hepatic portal vein. Pathological significance of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
65
0
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(68 citation statements)
references
References 113 publications
(112 reference statements)
1
65
0
2
Order By: Relevance
“…1). 8 Subcutaneous white adipose tissue (SAT) has different distribution according to gender. In men there is increased accumulation in the trunk compared to limbs, with a decreased rate and a more balanced distribution after the age of 50; in women, accumulation of SAT is similar +Model ENDONU-707; No.…”
Section: Adipose Tissue Characterization and Definitionmentioning
confidence: 99%
“…1). 8 Subcutaneous white adipose tissue (SAT) has different distribution according to gender. In men there is increased accumulation in the trunk compared to limbs, with a decreased rate and a more balanced distribution after the age of 50; in women, accumulation of SAT is similar +Model ENDONU-707; No.…”
Section: Adipose Tissue Characterization and Definitionmentioning
confidence: 99%
“…16 Conversely, lower body subcutaneous adiposity, characterized by adipose tissue accumulation between the hypodermis and muscle, is associated with cardioprotection, 17 lower glucose and triglycerides, higher HDL, insulin sensitivity and decreased risk for type-2-diabetes and metabolic syndrome. [18][19][20][21][22][23] Several factors differentiate visceral and subcutaneous adipose tissue, including adipokine and cytokine production, adipogenic potential and the ability to store and mobilize lipid (For review 24 ). Visceral adipose tissue, unlike subcutaneous depots, is also anatomically linked to the liver via the portal vein.…”
Section: Introductionmentioning
confidence: 99%
“…sents the remaining 15% [6]. It has been shown that an excessive accumulation of adipose tissue into the visceral compartment is associated with an increased risk for metabolic disorders [7][8][9][10].…”
mentioning
confidence: 99%